Honeybee-collected pollen from five Portuguese Natural Parks: palynological origin, phenolic content, antioxidant properties and antimicrobial activity - Morais, Margarida (2011)
The aim of this study was to determine the palynological origin, phenolic content, antioxidant and antimicrobial properties of pollen from five Portuguese Natural-Parks [Parque Nacional Peneda Gerês (PNPG); Parque Natural do Montesinho (PNM); Parque Natural do Alvão (PNA); Parque Natural da Serra da Estrela (PNSE) and Parque Natural do Douro Internacional (PNDI)]. Eight families were found in the mixture of bee pollen: Rosaceae, Cistaceae, Boraginaceae, Asteraceae, Fagaceae, Ericaeae, Myrtaceae and Fabaceae. The phenolic compounds content, determined by the Folin–Ciocalteu method, varied between 10.5 and 16.8 mg of gallic acid equivalents/g of extract (mg GAE/g) found in bee pollen from PNM and PNDI, respectively. The free radical scavenging measured showed the highest effective extract – PNM with EC50 2.16, followed by PND with 2.24 mg/mL. In the b-carotene bleaching assay the same behaviour as in the DPPH method was verified. We also verified that the presence of pollen differentially affected the growth of bacteria Gram-positive, Gram-negative and yeasts under study, depending this on the microorganism and the pollen used. This is an important study since, as far we know, it is the first time that Portuguese bee pollen from Natural Parks was studied, and their characterization can increase their economic value.